1997
DOI: 10.1007/s007050050219
|View full text |Cite
|
Sign up to set email alerts
|

THE non-structural polyprotein 3ABC of foot-and-mouth disease virus as a diagnostic antigen in ELISA to differentiate infected from vaccinated cattle

Abstract: A diagnostic assay to differentiate antibodies induced by foot-and-mouth disease virus (FMDV) infection from those induced by vaccination was developed. The test is an indirect-trapping ELISA which uses a monoclonal antibody to trap the non-structural 3ABC-FMDV polypeptide expressed in E. coli. Experimental and field sera from naive, vaccinated and infected cattle were examined. Using the established threshold of 0.20 optical density units, the sensitivity of the assay was 100%, as all the experimental post-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
100
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 12 publications
1
100
1
Order By: Relevance
“…However, recent sampling conducted between 2007 and 2009 have indicated that despite the endemicity of FMD in Nigeria with its attendant production losses in livestock, very little is known about the epidemiology of FMD in Nigeria (Fasina et al, 2013). The prevalence of FMD can be determined serologically by measuring the antibody level to the 3ABC nonstructural protein (NSP) (De Diego et al, 1997). The objectives of this study were to determine the seroprevalence of FMD and to identify the risk factors associated with seropositivity of FMD in cattle from the north-central Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent sampling conducted between 2007 and 2009 have indicated that despite the endemicity of FMD in Nigeria with its attendant production losses in livestock, very little is known about the epidemiology of FMD in Nigeria (Fasina et al, 2013). The prevalence of FMD can be determined serologically by measuring the antibody level to the 3ABC nonstructural protein (NSP) (De Diego et al, 1997). The objectives of this study were to determine the seroprevalence of FMD and to identify the risk factors associated with seropositivity of FMD in cattle from the north-central Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…7 In such endemic areas, it is important to identify animals, whether vaccinated or not, in which replication of Footand-mouth disease virus (FMDV; order Picornavirales, family Picornaviridae, genus Aphthovirus) has taken place to eliminate potentially infective animals. 2,3,11 Recently, a number of in-house and commercial tests to identify infection within vaccinated livestock (i.e., the presence of viral carrier animals) were developed and evaluated. 4,10,12 These methods are theoretically based on the assumption that semi-purified, inactivated FMDV vaccines mainly consist of capsid (structural) proteins, and so they are less likely to elicit production of antibodies against nonstructural proteins (NSP).…”
mentioning
confidence: 99%
“…An antibody response against NSPs is only related to in vivo virus activity. 3,8 However, the NSPs used in these test procedures were primarily produced in expression systems by using either bacteria or baculovirus, and nonspecific reactions can be caused by the presence of antibodies in test animals against these expression vector antigens. 14,15 More recently, synthetic peptides that contained B-cell epitopes of FMDV NSP have been used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies have been applied to obtain antigen preparations of 3AB 123 and 3ABC, including their expression in Escherichia coli 1,2,5,7 or Baculovirus, 6,12 and the use of a synthetic peptide. 9 In addition, 1 group of workers have produced a recombinant form of 3AB1 associated with Glutathione S-transferase in a prokaryotic expression system, but the protein yield was very low in concentration.…”
mentioning
confidence: 99%